Novel analgesics in ambulatory surgical patients. Issue 6 (December 2018) - Iskander, Andrew; Gan, Tong J.
Abstract : Purpose of review: The increasing number of procedures done in the ambulatory surgical setting necessitates the need for analgesic modalities that enable the management of postsurgical pain with fast onset, predictable duration of action, and minimal need for management of undesirable side-effects. Recent findings: The novel strategies for administration of local anesthetics in the ambulatory setting include prolonging their analgesic action at the site of surgical trauma while reducing systemic effects that result from their metabolism. Development of opioids aims to address receptor sites that provide for modulation of pain perception while reducing systemic, central effects of μ-receptor agonism. Other, more titratable agents with analgesic properties are also addressed. Summary: Local anesthetics, opioids, and NSAIDS are the mainstay of multimodal analgesic management, and as such, improving their efficacy in the ambulatory surgical setting remains the primary focus. However, as knowledge of the modulating pathways involved in transduction of pain increases, newer agents that utilize this knowledge are also becoming more widely available.